Strukturalisme Genetik dalam Novel Alita @ Heart Karya Dewie Sekar - Fitria Andriani; Didi Yulistio; Agus Trianto (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2021)
The purpose of this study was to describe the structural and socio-cultural aspects of the novel Alita @ Heart by Dewie Sekar through the analysis of genetic structuralism. The approach used is a sociological approach using genetic structuralism analysis. The object of this research is the novel Alita @ Heart by Andrea Hirata. Data obtained by reading and note-taking techniques. The research instrument is the researcher assisted by data tabulation which explains the problem boundaries. The data were analyzed by the following steps: 1) reading and understanding the novel, 2) identifying the data, 3) examining the structural elements contained in the novel, 4) examining the social and cultural conditions of the people who lived at the time the literary work was created, 5) examining the background the author's social and cultural life that influences his world view on the creation of the novel, and 6) draw conclusions from the data obtained. From the results of this analysis, it can be seen that in the structural aspect, the grooves consist of open grooves, middle grooves, peak grooves, and closed grooves. In this novel there are four main characters, namely Alita, Yusa, Abel, and Gading. While additional characters include Mama, Papa, Delita, Dayana, Lee, Juno, Ava, Rama, and Aldo. The settings used include offices, kiosks, restaurants, homes, Bali, Surabaya, and Jakarta. Then, the time setting used is the past and everyday. In the aspect of social and cultural conditions of the people of Jakarta that is raised in this novel is the condition of the people who are trapped in a life full of busy work activities, traffic jams, and love.